دعوى مسؤولية الدولة ومسطرة مقاضاة الدولة - تكترى، علاء الدين (جامعة لونيسي علي البليدة 2 - مخبر التنمية الاقتصادية والبشرية, 2017)
The State, in general, with its administration, army, police, public institutions, dust communities, hospitals, educational institutions, camps and other facilities is run by individuals exposed to error and thus subjected to damage to others. The administrative responsibility of the administration is to compensate the injured persons. Administrative dispute did not know their way in the area of compensation to justice in France, but from Blanco's decision issued on 02.08.1873. In Morocco, under Chapter 79 of the contracts of the Code of Obligations in 08/12/1913 which authorized the issue of the public authority for the damage caused to others, as described in this chapter include: "The state and the municipalities are responsible for the damage directly resulting from the conduct of its departments and errors of self-interest to its users, "as authorized Chapter 80 of the same law to sue the state to bear the compensation for the damage caused as a result of personal fault of the employee if the latter is insolvent, as stated in the chapter:" the users of the state and municipalities are personally liable for damages resulting from Tdlashm or serious incident errors of them in the performance of their functions, "and May be a demand that the state and municipalities because of such damages only when the insolvency of staff responsible
الدولة بصفة عامة، بإداراتها وجيشها وشرطتها ومؤسساتها العمومية وجماعاتها الترابية ومستشفياتها ومؤسساتها التعليمية ومخيماتها وما إلى ذلك من المرافق يتم تسييرها من طرف أفراد معرضون للخطأ ومعرضون من ثم لإلحاق أضرار بالآخرين، حيث تقوم المسؤولية الإدارية التي تفرض على الإدارة تعويض المصابين بالأضرار التي تسببت لهم فيها. والمنازعة الإدارية لم تعرف في مجال التعويض طريقها إلى القضاء في فرنسا إلا انطلاقا من قرار بلانكو الصادر بتاريخ 8/02/1873. وفي المغرب، بمقتضى الفصل 79 من قانون الالتزامات والعقود المؤرخ في 12/08/1913 الذي أجاز مسألة السلطة العمومية عن الأضرار التي تلحقها بالآخرين، حيث ورد في هذا الفصل ما يلي: "الدولة والبلديات مسؤولة عن الأضرار الناتجة مباشرة عن تسيير إداراتها وعن الأخطاء المصلحية لمستخدميها"، كما أجاز الفصل 80 من نفس القانون مقاضاة الدولة لتتحمل التعويض عن الضرر الحاصل نتيجة الخطأ الشخصي للموظف إذا كان هذا الأخير معسرا، حيث ورد في الفصل ما يلي: "مستخدموا الدولة والبلديات مسؤولون شخصيا عن الأضرار الناتجة عن تدليسهم أو عن الأخطاء الجسيمة الواقعة منهم في أداء ووظائفهم"، ولا تجوز مطالبة الدولة والبلديات بسبب هذه الأضرار إلا عند إعسار الموظفين المسؤولين عنها
Keywords: مقاضاة الدولة; قوانين وتشريعات; المسؤولية المدنية